PALLIATIVE-CURATIVE SURGICAL INTERVENTIONS IN GASTRIC CANCER PATIENTS WITH LIVER METASTASES - R.Z. YULDOSHEV; D.Z. ZIKIRY AKHODZHAEV; M.T. RAKHMATOV; S.A. DILSHODOV; YO.I. AZ ATULLOEV; A.A. KHODZHAMKULOV (Avicenna Tajik State Medical University, 2018)
Objective: To assess the effectiveness of relatively curative surgical interventions in the treatment of patients with gastric cancer with metastases to the liver and to show the role of active surgical tactics in improving the quality of life of patients. Methods: The study included 28 patients with gastric cancer with metastases to the liver. Patients with type I and type II Borrmann's tumor growth (17 (85.7%) patients) were prevalent. It was found that in the predominant majority of patients had lesions of regional lymph nodes (91.6%). Detection of ultrasound and CT studies of enlarged retroperitoneal lymph nodes, lymph nodes of the aortocaval space, as well as massive invasion of the serous cover of the stomach with the extra organ component detected by laparoscopy, is a contraindication for performing simultaneous operations on the stomach and liver. In 14 (50%) patients,surgical interventions were carried out against the background of a complicated clinical course of gastric cancer: in the presence of pylorostenosis in 9 (32%) cases and torpid (sluggish) bleeding in 5 (17.85%) cases. Results: Analyzing the primary tumour and metastatic hearth in the liver, we came to the conclusion that gastric cancer with gastric metastases in the liver should be resected in cases of highly or moderately differentiated adenocarcinoma that has exophytic or mixed forms of growth, preferably with the intactness of the serous cover of the stomach. Practically in half of the patients in our series, the metastasis in regional lymph nodes are revealed,however, only in two, the defeat of lymph nodes of the second - order was diagnosed. Thus, "resectable" liver metastases can occur even at the N0 stages. In the studied group, patients with type I and II Borrmann's prevailed with type I and II, most of them showed the intestinal histological type of a tumour. Conclusion: Liver resection for gastric cancer metastases should be performed under the following conditions: the absence of other distant metastases (peritoneum, non-regional lymph nodes, etc.); performing "radial" gastrectomy with D2-D3 lymphadenectomy; the possibility of carrying out macroscopic radical resection of the liver; functional portability of the operation; physiological operability.